Maternal inheritance of BDNF deletion, with phenotype of obesity and developmental delay in mother and child. Issue 1 (21st November 2017) - Harcourt, Brooke E.; Bullen, Denise V. R.; Kao, Kung‐Ting; Tassoni, Daniella; Alexander, Erin J.; Burgess, Trent; White, Susan M.; Sabin, Matthew A.
Abstract : Childhood obesity is a significant world health problem. Understanding the genetic and environmental factors contributing to the development of obesity in childhood is important for the rational design of strategies for obesity prevention and treatment. Brain‐derived neurotrophic factor (BDNF) plays an important role in the growth and development of the central nervous system, there is also an evidence that BDNF plays a role in regulation of appetite. Disruption of the expression of this gene in a child has been previously reported to result in a phenotype of severe obesity, hyperphagia, impaired cognitive function, and hyperactivity. We report a mother and child, both with micro‐deletions encompassing the BDNF gene locus, who both have obesity and developmental delay, although without hyperactivity. This report highlights the maternal inheritance of a rare genetic cause of childhood obesity.